A laboratory study of low-frequency wave dispersion and attenuation in water-saturated sandstones - Mikhaltsevitch, Vassili; Lebedev, Maxim; Gurevich, Boris (Society of Exploration Geophysicists, 2014)
Laboratory measurements of elastic and anelastic parameters of dry and water-saturated sandstones with low (0.7- and 1.1-mD) and high (425-mD) permeability have been conducted at seismic frequencies (0.1 to 120 Hz). The experiments were performed with a laboratory apparatus that measures the stress-strain relationship in the linear regime. The extensional attenuation in water-saturated low-permeability sandstones exhibits prominent peaks in the seismic band, accompanied by considerable dispersion. Variations in attenuation and dispersion in the high-permeability sandstone are below the measurement error, as is the moduli dispersion in all the sandstones in dry condition. The experiments demonstrate that for low-permeability rocks, seismic frequencies do not necessarily correspond to the low-frequency limit (relaxed pore-fluid pressures) of acoustic wave dispersion.